Maria G. Castro: science is a highly collaborative endeavor that transcends different barriers! - Li, Brad (Translational Cancer Research; Vol 7, No 5 (October 31, 2018): Translational Cancer Research, 2018)
Brain cancer is one of the deadliest cancers among children and adults under 40. Just in the United States alone, an estimate of approximately 23,000 adults and 3,000 children will be diagnosed with a brain or central nervous system (CNS) tumor in 2018 (1).